Phosphonic acid based polymeric fluorescent sensor for Hg(II) analysis - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (ELSEVIER SCIENCE SA, 2016)
In this study, vinyl phosphonic acid based highly selective fluorescent sensor was developed for Hg(II) detection in aqueous solution. The sensor showed preferable fluorescence response to mercury ions. Various experimental parameters, such as pH, response time were investigated. The developed sensor showed satisfactory reversibility, reproducibility and response time. The proposed sensor possesses relatively long short term stability of at least 8 h and a life time of 3 months. Working concentration range of the sensor was found to be 2.5 x 10(-8) mol L-1 to 2.5 x 10(-7) mol L-1 and detection limit for mercury ions was 1.3 x 10(-8) Mol L-1. Additionally, the proposed fluorescence sensor was successfully applied to quantitatively determine the amount of mercury in tap water and satisfactory results were obtained. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Selective Hg(II) determination; Fluorimetric sensor; Vinyl phosphonic acid; Photo-curing; FLUOROMETRIC-DETERMINATION; TRACE AMOUNTS; BULK OPTODE; MERCURY; SPECTROMETRY; CHEMOSENSOR; SAMPLES; WATER; FISH; PORPHYRIN